2021
DOI: 10.1007/s12015-021-10242-7
|View full text |Cite
|
Sign up to set email alerts
|

Human Adipose-Derived Mesenchymal Stromal Cells Exhibit High HLA-DR Levels and Altered Cellular Characteristics under a Xeno-free and Serum-free Condition

Abstract: Background We have observed an increased expression of negative markers in some clinical-grade, xeno- and serum-free cultured adipose-derived mesenchymal stem/stromal cell (ADMSC) samples. It gave rise to concern that xeno- and serum-free conditions might have unexpected effects on human ADMSCs. This study aims to test this hypothesis for two xeno- and serum-free media, PowerStem MSC1 media (PS) and StemMACS MSC Expansion Media (SM), that support the in vitro expansion of ADMSCs. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…ASCs, and mesenchymal stem cells in general, have long been considered hypoimmunogenic because of the absence of HLA class II, low expression of HLA class I and co-stimulatory molecules such as CD40 and CD80. However, some studies have highlighted that ASCs can become more immunogenic during cell expansion in vitro, depending on culture conditions, 67 , 68 and may induce cellular and humoral responses when used in an allogeneic setting. 69 , 70 Complement activation properties have also been reported.…”
Section: From Bench To Clinical Implementation: Scientific Challengesmentioning
confidence: 99%
“…ASCs, and mesenchymal stem cells in general, have long been considered hypoimmunogenic because of the absence of HLA class II, low expression of HLA class I and co-stimulatory molecules such as CD40 and CD80. However, some studies have highlighted that ASCs can become more immunogenic during cell expansion in vitro, depending on culture conditions, 67 , 68 and may induce cellular and humoral responses when used in an allogeneic setting. 69 , 70 Complement activation properties have also been reported.…”
Section: From Bench To Clinical Implementation: Scientific Challengesmentioning
confidence: 99%
“…Subsequently, the CD markers profile of rBM-MSCs were checked using flow cytometry. There are some reports regarding aged-associated lessening of CD markers profile [ 104 , 105 ]. Moreover, some publications reported that MSCs surface markers decrease in higher passages [ 106 ] which subsequently, reduces the stemness and differentiation capacity and as a result, decreases the quality of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…HLA-DR belongs to the major histocompatibility complex class II and plays a crucial role in host immune responses. Previous reports suggest that HLA-DR could change the karyotypes and cause earlier senescence of MSCs ( Dam et al, 2021 ). Additionally, HLA-DR-expressing MSCs may increase the risk of an alloimmune response ( Kot et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%